'And I would ask myself, what's being gay got to do with this anyway?' Constructions of queer subject positions in student's stories. (March 2023) - Francis, Dennis A
In this paper, the author explores some of the issues associated with teaching about compulsory heterosexuality and schooling in an undergraduate sociology programme. Using a novel approach to gathering data, the article analyses the stories students submitted about themselves or others who were counter normative in terms of gender and sexuality in school. Informed by the work of Ahmed and Foucault, this article explores what kinds of gendered and sexualised subject positions become possible through the stories of students, and how are these subject positions interpellated and constituted relationally? Despite progressive legislation, queer activism and the significant visibility of gender and sexuality counter-normative identities in the South African media, the analysis highlights that students' position school attending queer youth as (1) stereotyped caricatured subjects, (2) objects of fear and (3) subjects of violence. These subject positions serve as straightening devices that interpellate queer school attending youth as unfamiliar, not belonging and unworthy and therefore requiring change. Insights from this article can inform the research and practice which is pivotal to addressing cisheteronormativity not only in schools but cultural ideas, norms and practices too.